The support of the diplomatic and consular network to the new Spanish emigration: role of the current ministries of labor, migration and social security abroad - Esteban de la Rosa, Gloria (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The Spanish economy continues to be based almost mainly on the services sector and construction and, therefore, cheap labor continues to be the main employment of young people, who, however, want to find an occupation that is in line with their training. A study is carried out on the role played by the Labor, Migration and Social Security Ministries in order to protect the social and labor of Spaniards who emigrate abroad, especially after the ministerial remodeling carried out by the Government of Spain (Ministry of Inclusion, Social Security and Migrations, on the one hand, and Ministry of Labor and Social Economy, on the other). And this in a historical context and in the regulatory framework provided by Law 2/2014, of March 25, on Action and the Foreign Service of the State and Law 40/2006, of December 14, of the Statute of Spanish citizenship abroad .